Efficacy and tolerability of 1.6% phenol-croton peeling vs. topical 5% imiquimod in the treatment of actinic cheilitis: a randomized controlled trial - Garbers, Luiz Eduardo Fabrício De Melo; Miola, Anna Carolina; Souza, Vinicius de; Brommonschenkel, Christina de Castro; Lima, Flavio de Oliveira; Minicucci, Eliana Maria; Miot, Helio Amante (Oxford University Press (OUP), 2024)
BACKGROUND: Trials evaluating the effectiveness of topical treatments for actinic cheilitis (AC) are scarce. Despite no comparative data, phenol-croton peeling has been reported as effective in treating this condition. OBJECTIVE: To assess for the treatment of AC the efficacy and tolerability of a single session of 1.6% phenol-croton peeling vs. topical 5% imiquimod cream applied for 30 days for the treatment of AC. METHODS: An open, randomized controlled trial was conducted to compare the effectiveness and tolerability of 1.6% phenol-croton peeling vs. topical 5% imiquimod for the treatment of AC [protocol registered at ReBEC (Brazilian Registry of Clinical Trials) - RBR-1044sz68]. Thirty-six patients with biopsy-proven AC were allocated into two groups (1 : 1): the imiquimod group received 5% topical imiquimod three times a week for 30 days, and the croton group underwent one session of 1.6% phenol-croton peeling. The primary outcome was the clearance of AC after 56 days. Secondary outcomes included clinical and histological parameters, adverse effects and clinical results after 180 days. RESULTS: Complete clinical clearance of AC (defined as clearance of both leukoplakia and hyperkeratosis) at day 56 and day 180 occurred in 17 of 18 (94%) participants from the croton group but in none of the 18 participants in the imiquimod group (P < 0.01). Improvement in all clinical parameters was more prominent in the croton group (P ≤ 0.01). Complete histological normalization at day 56 occurred in 72% of the croton group and only 17% in the imiquimod group (P < 0.01). Histological parameters such as atypia (keratinocyte intraepithelial neoplasia score), solar elastosis and hyperkeratosis reduced in intensity only in the croton group (P < 0.05). Adverse effects were most intense on day 7 in the croton group and persisted until day 21 in the imiquimod group. The study was prematurely terminated at the interim analysis. CONCLUSIONS: A single session of 1.6% phenol-croton peeling produced clinically and histologically superior results with a shorter recovery period compared with imiquimod for treating AC.